The Relationship between Limb Muscle Strength and Football Passing Skills at SSB Bengkulu Raya - Restu Nanda Ariesta; Azizatul Banat (Penerbit Jurnal Indonesia, 2021)
This study aims to: determine the relationship between leg muscle strength and passing skills in soccer games at SSB Bengkulu Raya. The approach method used in this research is to use the correlation method with the type of quantitative research, namely research based on calculations in the form of numbers using statistical calculations. The population in this study were 20 athletes. The sampling technique in this study used a side total technique, namely the sampling technique taking all members of the population as samples or respondents, namely 20 people. The data collection used in this study was by using a vertical jump test and a football passing test. The data analysis technique used in this research is the Product Moment Correlation analysis technique. From the results of the analysis using the Product Moment Correlation, the calculated r value = 0.548. When compared with the value of r table with a significance of 5% at n = 20, found a value of 0.444. From this value, it is known that r arithmetic is smaller than r table (0.548> 0.444), then Ha is accepted and Ho is rejected, meaning that in this study there is a relationship between leg muscle strength and passing skills in soccer games at SSB Bengkulu Raya.